Presence of anti-nuclear antibody associated with worse clinical outcomes of anti-NMDAR encephalitis - Lei, Chunyan; Li, Yongyu; Li, Haijiang; Zhu, Xiaoyan; Jiang, Wen; Chang, Xiaolong (Frontiers in Neurology, 2022)
Purpose: Systemic autoantibodies are important for the diagnosis of autoimmune diseases, but their roles in anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis are unknown. The purpose of our study is to investigate the characteristics and prognosis of anti-NMDAR encephalitis with the prevalence of autoantibodies. Methods: Systemic autoantibodies were evaluated in 64 patients with anti-NMDAR encephalitis and 14 patients with autoimmune encephalitis with other forms. Then according to systemic autoantibodies, patients with anti-NMDAR encephalitis were divided into anti-nuclear antibody (ANA) positive group and ANA negative group. The clinical outcome was assessed by a modified Rankin score at 12 months after the disease onset. Results: A total of 64 anti-NMDAR encephalitis patients were enrolled, of which 28.13% (18/64) were positive for ANA. The titers of positive anti-NMDAR antibody in CSF (P=0.041) and serum (P=0.031) in the ANA positive group was significantly higher than ANA negative group. Patients with ANA positive than those with ANA negative showed lower rates of headache (P=0.047) and speech disorder (P=0.049). The presence of ANA was associated worse clinical outcome at 12-month (P=0.043). Conclusion: ANA was prevalent in patients with anti-NMDAR encephalitis, and associated with worse prognosis and impaired neurological recovery.